Metal injection molding as enabling technology for the production of metal prosthesis components: Electrochemical and in vitro characterization. Issue 7 (10th May 2013) - Melli, Virginia; Rondelli, Gianni; Sandrini, Enrico; Altomare, Lina; Bolelli, Giovanni; Bonferroni, Benedetta; Lusvarghi, Luca; Cigada, Alberto; De Nardo, Luigi
Abstract Industrial manufacturing of prosthesis components could take significant advantage by the introduction of new, cost‐effective manufacturing technologies with near net‐shape capabilities, which have been developed during the last years to fulfill the needs of different technological sectors. Among them, metal injection molding (MIM) appears particularly promising for the production of orthopedic arthroplasty components with significant cost saving. These new manufacturing technologies, which have been developed, however, strongly affect the chemicophysical structure of processed materials and their resulting properties. In order to investigate this relationship, here we evaluated the effects on electrochemical properties, ion release, and in vitro response of medical grade CoCrMo alloy processed via MIM compared to conventional processes. MIM of the CoCrMo alloy resulted in coarser polygonal grains, with largely varying sizes; however, these microstructural differences between MIM and forged/cast CoCrMo alloys showed a negligible effect on electrochemical properties. Passive current densities values observed were 0.49 µA cm−2 for MIM specimens and 0.51 µA cm−2 for forged CoCrMo specimens, with slightly lower transpassive potential in the MIM case; open circuit potential and Rp stationary values showed no significant differences. Moreover, in vitro biocompatibility tests resulted in cell viability levels not significantly different for MIM and conventionally processed alloys. Although preliminary, these results support the potential of MIM technology for the production of CoCrMo components of implantable devices. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 101B: 1294–1301, 2013.